MICROCLIMATE VARIATION AMONG FOUR COMMON URBAN TREE SPECIES IN CALABAR, NIGERIA - Ononyume, Martin Ogheneriruona; Edu, Esther Aja Bassey (FUDMA JOURNAL OF SCIENCES, 2026)
Rapid urbanization in Calabar is increasing heat stress, but detailed evidence on how urban trees control microclimate remains scarce. This study measured temperature and relative humidity (RH) beneath four common urban tree species in Calabar using a temperature and relative humidity meter. Data were collected from Azadirachta indica, Albizia lebbeck, Delonix regia, and Terminalia mantaly canopies, as well as from nearby open areas, during morning and afternoon periods. Linear mixed-effects models revealed strong daily fluctuations: afternoon temperatures were 3.22°C higher than in the morning (SE = 0.20; p < 0.001), while RH decreased by 9.36% (SE = 0.41; p < 0.001). Canopy shading consistently moderated these effects, lowering temperature by 0.81°C (SE = 0.20; p < 0.001) and raising RH by 2.52% (SE = 0.41; p < 0.001). Differences between species were generally minor; Azadirachta indica was slightly cooler than Albizia lebbeck (−0.408°C; p = 0.044) and showed a smaller afternoon RH decrease (+1.52%; p = 0.009). Most interactions were not significant, suggesting microclimate effects were broadly similar across species. The models accounted for a large portion of variation (Temperature marginal R² = 0.78; RH marginal R² = 0.91). Although boundary (singular) fits and short-term sampling limit the broad applicability of species-specific results, diagnostics confirmed the reliability of key fixed effects. Overall, the findings show that canopy cover, more than species type, determined microclimate buffering in Calabar and emphasize the importance of expanding and preserving urban tree cover to reduce heat.
Keywords: Thermal regulation; Urban trees; Canopy shading; Tropics; Urban greening